Microbial communities and lipid records of the Linxia Basin, NE Tibetan Plateau: Implications for enhanced aridity in the Late Miocene. (15th May 2020) - He, Wei; Wang, Gen; Wang, Yongli; Wei, Zhifu; Huang, Zhiyong; Zhang, Ting; Ma, Xueyun; Ma, He; Yu, Xiaoli
Graphical abstract: Highlights: There is a continuous paleoclimatic records since 29 Ma in the Linxia Basin. The evolution of microbes is used to demonstrate fast stepwise drying of the Linxia Basin at around 8 Ma. Microbial community could serve as a potential indicator of paleoclimate reconstruction. Abstract: The Linxia Basin on the north-eastern Tibetan Plateau in northwest China bears continuous and thick lacustrine-fluvial sediments with environmental significance to central Asian aridification. However, limited efforts have been made on investigating the microbial community evolution, even though lipid biomarkers have been successfully employed to reconstruct paleoenvironmental conditions in this area. This study used the ancient DNA and n- alkanes preserved in the lacustrine-fluvial sediments from the Linxia Basin, and employed high throughput sequencing and geochemical analyses to understand the climatic conditions spanning the past 29 million years. The characteristics of n -alkanes indicate that the organic matter was derived from mixed sources (bacteria, algae, and higher plants), and a series of n -alkane proxies (ACL, n -C21 − / n -C22 +, Paq, and Pwax) established that the climate shifted to arid conditions at approximately 8 Ma. It is noteworthy that the relative abundance trends of two classes of microbes (Proteobacteria and Firmicutes) were negatively correlated. Furthermore, the increasing Firmicutes and the relatively decreasing Proteobacteria at approximately 8 Ma also corroborated this arid event. In addition, during this period, there was an extremely low abundance of archaea, which might correspond to severe climatic conditions around 8 Ma. Therefore, this study suggests that the microbial communities could serve as a potential tool for the reconstruction of paleoenvironments.